Lysophosphatidylcholine increases rat ileal permeability to macromolecules. Issue 4 (April 1985) - Tagesson, C; Franzén, L; Dahl, G; Weström, B
Abstract : The influence of lysophosphatidylcholine (LPC) on macromolecular permeability in the distal ileum has been studied. Using a rat experimental model, we determined the intestinal permeability to different sized dextrans (3000-70 000 daltons) and bovine serum albumin (BSA) in the absence and presence of LPC. We also examined the morphology of the ileal mucosa after deposition of LPC in the gut lumen, and determined N-acetyl-beta-glucosaminidase, 5'-nucleotidase, and alkaline phosphatase activities in suspensions of isolated mucosal cells and different concentrations of LPC. We found that 20 mM LPC damaged the ileal mucosa and that it increased its permeability to all the molecules investigated. Moreover, mixtures of mucosal cells and 0.01-1 mM LPC showed increased N-acetyl-beta-glucosaminidase activity: the higher the LPC concentration, the higher the enzyme activity. These findings indicate that LPC, a naturally occurring surfactant in the intestine, might damage mucosal cells and release lysosomal enzyme activity, and that higher LPC concentrations may impair the mucosal barrier function and increase the gut permeability to macromolecules such as proteins. This could have relevance to the development of various disease states, in which increased intestinal absorption of macromolecules is of importance.